2020
DOI: 10.26434/chemrxiv.12616178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Chemical Probe for Dark Kinase STK17B Derives its Potency and High Selectivity Through a Unique P-loop Conformation

Abstract: We present the discovery of thieno[3,2-<i>d</i>]pyrimidine <b>SGC-STK17B-1</b> (<b>11s</b>), a high-quality chemical probe for this understudied “dark” kinase. <b>11s</b> is an ATP-competitive inhibitor that showed remarkable selectivity over other kinases including the closely related STK17A. X-ray crystallography of <b>11s</b> and related thieno[3,2-<i>d</i>]pyrimidines bound to STK17B revealed a unique P-loop conformation charac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The dual specificity tyrosine‐phosphorylation‐regulated kinase 2 (DYRK2) inhibitor harmine, the Janus kinase 1 (JAK1) inhibitor baricitinib and the dual inhibitor KH‐CB19 for cdc‐like kinase 1 and 4 (CLK1 and CLK4) were purchased from Santa Cruz Biotechnology (Dallas, TX, USA), and the death‐associated protein kinase 3 (DAPK3) inhibitor HS38 was obtained from Tocris Bio‐Techne (Bristol, UK). The dual inhibitor SGC‐AAK1‐1 18 against BMP‐2‐inducible kinase (BMP2K) and AP2‐associated protein kinase 1 (AAK1), the inhibitor SGC‐STK17B‐1 18 against serine/threonine kinase 17B (STK17B) and UNC‐AP‐194 for serine/threonine‐protein kinase haspin (GSG2) inhibition were kindly provided from the group of Prof. Dr Stefan Knapp (Structural Genomics Consortium at the Goethe University Frankfurt). Cycloheximide (CHX) was purchased from Sigma‐Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The dual specificity tyrosine‐phosphorylation‐regulated kinase 2 (DYRK2) inhibitor harmine, the Janus kinase 1 (JAK1) inhibitor baricitinib and the dual inhibitor KH‐CB19 for cdc‐like kinase 1 and 4 (CLK1 and CLK4) were purchased from Santa Cruz Biotechnology (Dallas, TX, USA), and the death‐associated protein kinase 3 (DAPK3) inhibitor HS38 was obtained from Tocris Bio‐Techne (Bristol, UK). The dual inhibitor SGC‐AAK1‐1 18 against BMP‐2‐inducible kinase (BMP2K) and AP2‐associated protein kinase 1 (AAK1), the inhibitor SGC‐STK17B‐1 18 against serine/threonine kinase 17B (STK17B) and UNC‐AP‐194 for serine/threonine‐protein kinase haspin (GSG2) inhibition were kindly provided from the group of Prof. Dr Stefan Knapp (Structural Genomics Consortium at the Goethe University Frankfurt). Cycloheximide (CHX) was purchased from Sigma‐Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This observation further highlights the importance of the two methoxy groups for PfPK6 inhibition, which could almost fully compensate for the detrimental 3-position N atom. Similar to 23, incorporation of a nitrogen atom at the equivalent positions of thieno [3,2-b] Additionally, attempts at the removal of the annulated phenyl ring completely and replacing it with a chloro substituent (32, 33 and 34) were found not to be tolerated by PfPK6, while addition of a benzylamino substituent on the 6-position of the pyrimidine (35) resulted in only a modest improvement in PfPK6 potency over 31.…”
Section: Sar Of Hinge-binding Regionmentioning
confidence: 99%
“…Our group has previously shown that the configuration of atoms on heterocycles bearing the hingebinding N atom influences its pKa, which is paramount for effective ligand-kinase molecular recognition 35 . Using density functional theory (DFT) [36][37][38] , we predicted the pKa for each hinge-binding N atom on heterocycles tested (Table S3).…”
Section: Sar Of Hinge-binding Regionmentioning
confidence: 99%
See 2 more Smart Citations